TINDAKAN HUKUM PUBLIK MENGENAI BELEIDSREGEL PEMERINTAH DAERAH PROVINSI RIAU TERHADAP MODA TRANSPORTASI ONLINE DI KOTA PEKANBARU TAHUN 2018-2019 - Yanri Imanuel Siagian; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The state in creating welfare performs its duties and functions, which is represented by the government as an element that has the power to regulate and administer the government system. The government in carrying out its duties and functions is given the right to take an action based on the prevailing laws and regulations. However, not all aspects of human life in the administration of government can be regulated through existing laws, therefore discretionary authority is needed to overcome these problems. In the context of transportation in the city of Pekanbaru, there is a conflict between conventional transportation drivers and online transportation drivers because many online transportation drivers are still illegal. To resolve this problem, the Minister of Transportation Regulation Number 118 of 2018 concerning the Implementation of Special Rental Transportation does not contain operational standards on how to take legal action for these illegal drivers. Therefore, it requires public legal action by beleidsregel to fill the legal void regarding standard operational actions. However, what happened was that the Riau Province Transportation Agency did not use the authority of the beleidsregel because of several factors that influenced it.            This study aims to explain the factors that caused the Regional Government of Riau Province to choose not to take public legal action against the law on online transportation modes in the city of Pekanbaru in 2018-2019. The location of this research was conducted at the Riau Province Transportation Service Office. Furthermore, data collection techniques are carried out by interview, documentation and literature study.            The results of this study indicate that the Riau Province Department of Transportation chose not to take legal action to online transportation modes in the city of Pekanbaru 2018-2019 due to several factors such as the economic impact of the community caused by the large number of illegal online transportation operations that will be stopped because it is not based on Minister of Transportation Regulation No. 118 of 2018 concerning the Implementation of Special Lease Transportation, the absence of digital data on the dashboard of the applicator at the Riau Province Transportation Service makes prosecution very difficult to carry out, and the use of beleidsregel which is prone to abuse of authority makes the Riau Province Transportation Office reluctant to take this legal action.Keywords: Legal Action, Online Mode of Transportation, Applicator, Digital         Dashboard.